Pengembangan Teknik Komunikasi Kader dalam Memberikan Penyuluhan Balita Stunting - Hamzah, Wardiah; Syam, Nasruddin; Sartika (Window of Community Dedication Journal, 2021)
Cadres as the spearhead of activities at the Posyandu must be able to provide counseling to the public about stunting by using communication techniques that are acceptable to the people who come to the Posyandu. However, not all cadres can carry out communication and counseling techniques to the community. Community service aims to develop communication techniques for Posyandu cadres in providing counseling for stunting toddlers with training methods in Borisallo Village which was attended by 20 posyandu cadres who were evaluated using a pre-post test. The results of the training showed an increase in the ability of Posyandu cadres in communication techniques and an increase in the ability of Posyandu cadres in providing counseling for stunting toddlers.